2004
DOI: 10.1016/s1607-551x(09)70108-1
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Chemoattracted by Eotaxin from Cerebrospinal Fluid of Mice Infected with Angiostrongylus Cantonensis Assayed in a Microchamber

Abstract: When non-permissive hosts are infected with Angiostrongylus cantonensis, the migration of the worms to the brain and their subsequent development manifests as marked eosinophilic pleocytosis. We used microchambers to demonstrate direct eosinophil chemotactic activity by adding a variety of antibodies into cerebrospinal fluid (CSF) of BALB/c mice 21 days post-infection with A. cantonensis. The antibodies were directed to neutralize eotaxin, RANTES (regulated on activation, normal T-cells expressed and secreted)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Although increased CSF CCL11 and CXCL10 levels in ME/CFS subjects, along with dysregulation of IL1 signaling, suggest the possibility of an allergic process in central compartments, 49,50 such patterns may also be seen in a wide range of CNS infections. [51][52][53][54] Additional studies focused on delineating the relationships of clinical phenotypes of ME/CFS to immune profiles in both the CSF and the peripheral blood are of paramount importance to investigating potential causes and biomarkers for disease. Recent reports indicate regional changes in white matter volume 19 and abnormalities in myelin in white matter tracts in ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…Although increased CSF CCL11 and CXCL10 levels in ME/CFS subjects, along with dysregulation of IL1 signaling, suggest the possibility of an allergic process in central compartments, 49,50 such patterns may also be seen in a wide range of CNS infections. [51][52][53][54] Additional studies focused on delineating the relationships of clinical phenotypes of ME/CFS to immune profiles in both the CSF and the peripheral blood are of paramount importance to investigating potential causes and biomarkers for disease. Recent reports indicate regional changes in white matter volume 19 and abnormalities in myelin in white matter tracts in ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, BBB disruption during eosinophilic meningitis involves a complex interaction between eosinophils and mediators, such as interleukin-4, interleukin-5, platelet-activating factor, nitric oxide, and matrix metalloproteinases, which might induce BBB permeability, independent of HGF. 9,[28][29][30] In conclusion, we found that patients with eosinophilic meningitis had elevated HGF levels in the CSF. The clinical significance needs to be clarified further.…”
mentioning
confidence: 48%
“…A total of 1000 cells from multiple fields were examined for each slide. Counts of total cells, eosinophils, macrophage, neutrophils, and lymphocytes were performed on blinded samples, as described previously [69].…”
Section: Bronchoalveolar Lavage Collection and Cell Countingmentioning
confidence: 99%